Building a sentinel surveillance system for sexually transmitted infections in Germany, 2003. Issue 2 (30th March 2005) - Bremer, V; Marcus, U; Hofmann, A; Hamouda, O
Abstract : Background/objectives: Increases in STIs have been reported from the United States and Europe. Since 2001, only syphilis and HIV are notifiable in Germany. A sentinel surveillance system has been set up to assess the occurrence and trends of STIs and identify risk groups. Methods: Through the sentinel system data are collected from local health offices (LHO), hospital based STI clinics and private practitioners (dermato-venerology, urology, gynaecology, or HIV). For every newly diagnosed laboratory confirmed infection of HIV, gonorrhoea, chlamydia, syphilis, or trichomoniasis physicians complete a standardised questionnaire regarding diagnosis, source of infection, and demographic information. Patients complete a questionnaire about sexual risk behaviour. The patient form is matched with the diagnosis form using a unique identifier number. Characteristics of sentinel patients were compared with those reported through the HIV and syphilis national notification system. Results: 58 LHO, 14 hospital based STI clinics, and 160 private practitioners (53.1% dermato-venerologists) from all federal states participated in the study. 176 (75.9%) sentinel sites are located in cities of >100 000 inhabitants. From 1 March 2003–29 February 2004, a total of 1833 STIs have been reported, among them 452 chlamydia, 321 syphilis (10.9% of notified syphilis), 343 gonorrhoea, 269 HIV (15.7% of notified HIV). 925 (50.5%) of the patients were male, the median age was 31 years. Female patients were more often of foreign origin (χ 2 test; 70.0% v 26.3%; p<0.001). Conclusions: Our sentinel system will provide a base for detection of STI trends in Germany. In addition, information about sexual risk behaviour will enable us to target prevention at those most at risk for STIs.